Dynamics of adrenal glucocorticoid steroidogenesis in health and disease. (15th June 2015) - Spiga, Francesca; Lightman, Stafford L.
Highlights: A feedforward–feedback loop between the anterior pituitary and adrenal glands generate glucocorticoids ultradian rhythm. Ultradian rhythm of glucocorticoids depends on highly dynamic processes within adrenocortical steroidogenic cells. Disruption of these dynamics leads to abnormal glucocorticoid secretion observed in disease and critical illness. Abstract: The activity of the hypothalamic–pituitary–adrenal (HPA) axis is characterized by an ultradian (pulsatile) pattern of hormone secretion. Pulsatility of glucocorticoids has been found critical for optimal transcriptional, neuroendocrine and behavioral responses. This review will focus on the mechanisms underlying the origin of the glucocorticoid ultradian rhythm. Our recent research shows that the ultradian rhythm of glucocorticoids depends on highly dynamic processes within adrenocortical steroidogenic cells. Furthermore, we have evidence that disruption of these dynamics leads to abnormal glucocorticoid secretion observed in disease and critical illness in both humans and rats.